2008
DOI: 10.1105/tpc.106.049478
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Regulation of TPS04/GES, anArabidopsisGeranyllinalool Synthase Catalyzing the First Step in the Formation of the Insect-Induced Volatile C16-Homoterpene TMTT

Abstract: Volatile secondary metabolites emitted by plants contribute to plant-plant, plant-fungus, and plant-insect interactions. The C 16 -homoterpene TMTT (for 4,8,12-trimethyltrideca-1,3,7,11-tetraene) is emitted after herbivore attack by a wide variety of plant species, including Arabidopsis thaliana, and is assumed to play a role in attracting predators or parasitoids of herbivores. TMTT has been suggested to be formed as a degradation product of the diterpene alcohol (E,E)-geranyllinalool. Here, we report the id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

4
170
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 145 publications
(175 citation statements)
references
References 78 publications
(97 reference statements)
4
170
0
1
Order By: Relevance
“…As previously demonstrated in accession Col-0, coronalon induces the emission of MeSA, (E,E)-a-farnesene, the homoterpene TMTT, and its precursor geranyllinalool, a response similar to that observed upon feeding damage by larvae of P. xylostella (Herde et al, 2008). By comparing emissions of volatile terpenes from leaves of intact plants treated with coronalon for 22 to 30 h, we found that 20 accessions released the monoterpene (E)-b-ocimene as the predominant volatile (approximately 75%-95% of the total amount of volatiles) at rates differing 80-fold between lowest and highest emitters (Table I).…”
supporting
confidence: 50%
See 4 more Smart Citations
“…As previously demonstrated in accession Col-0, coronalon induces the emission of MeSA, (E,E)-a-farnesene, the homoterpene TMTT, and its precursor geranyllinalool, a response similar to that observed upon feeding damage by larvae of P. xylostella (Herde et al, 2008). By comparing emissions of volatile terpenes from leaves of intact plants treated with coronalon for 22 to 30 h, we found that 20 accessions released the monoterpene (E)-b-ocimene as the predominant volatile (approximately 75%-95% of the total amount of volatiles) at rates differing 80-fold between lowest and highest emitters (Table I).…”
supporting
confidence: 50%
“…4C). Moreover, no changes were observed for the induced transcription of the TPS02 pseudogene and the (Herde et al, 2008), these results strongly suggested that the TPS03 gene is responsible for the induced formation of (E,E)-a-farnesene in the Col-0 accession.…”
mentioning
confidence: 58%
See 3 more Smart Citations